Changes and Continuities in Citizenship Education: What kind of Citizenship Education does the 2018 Social Studies Programme of Study Envisage? - Abdulkerim Şen (Anı Publishing, 2019)
Citizenship education was influenced by fundamental changes that happened following the end of the Cold War in 1989. Traditional citizenship education aiming to build a monolithic national identity, disseminate an image of homogeneous society and transmit the knowledge of political system has evolved towards modern citizenship education characterised by an emphasis on human rights, democracy, the rule of law, respect for diversity and a concern to develop students' political participation skills. The transition to modern citizenship education in Turkey started with the pushing of international educational projects and is still underway. Drawing on critical discourse analysis, this study explores what kind of citizenship education the 2018 Social Studies Courses Programme of Study envisages. The study found that the new programme intensely reflects the characteristics of traditional citizenship education. Taking into account this study's findings might lead to more effective implementation of the programme and increase the success of future curriculum reforms.